Responsivitas pelayanan perusahaan umum daerah (perumda) air minum dalam melayani pemasangan Sambungan baru (Studi Pada Perumda Tirta Hidayah Kota Bengkulu) - Aprianti, Resi Dwi; Lorita, Evi; Saputra, Harius Eko (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This study aims to determine how the responsiveness of Regional Public Company Services (Perumda) Drinking Water Tirta Hidayah Bengkulu city in serving the new installation. This research uses a qualitative descriptive method. Data collection using observation, interview, and documentation techniques. Data analysis techniques use data reduction, data presentation and verification or making conclusion. The results showed that the responsiveness of Perumda Drinking Water Tirta Hidayah Bengkulu city in serving the new installation consisted of 5 (five) things, namely: (1) the presence or absence of complaints from users in the past year. In this case there are indeed complaints from users of new installation services related to the length of time for installation which is not in accordance with what was delivered by the officer; (2) The attitude of the officers in responding to the complaints has tried to serve as much as possible by being friendly, polite and courteous to users of new installation services; (3) Use of complaints as a reference for further service improvement. In this case the officers certainly make complaints from customers as a reference for further service improvement and find solutions to customer complaints; (4) The various actions of officers in providing satisfaction with new installation services are to reply to every complaint from incoming customers both online and verbally and innovate in conducting online services Sejam Ladas (One Hour Report Follow Up Completed); (5) Placement of service users in the service system is placed based on the order of the new installation registration queue.